The Relationship between Knowledge and Chronic Kidney Failure Prevention Behavior in Hypertensive Patients at Limboto Health Center - Dwi Ayu Novelita; Nurdiana Djamaluddin; Sitti Fatimah M. Arsad (Universitas Muhammadiyah Palu, 2026)
Uncontrolled hypertension can cause various serious complications, one of which is chronic kidney failure (CKD). Hypertensive patients' knowledge of their disease plays an important role in the prevention behavior of complications such as chronic kidney failure. Good knowledge is characterized by an understanding of risk factors, the importance of blood pressure control, adherence to taking medications, as well as a healthy lifestyle such as a low-salt diet and regular exercise that can prevent complications, one of which is chronic kidney failure. This study aims to analyze the relationship between knowledge and chronic kidney failure prevention behavior in hypertensive patients at the Limboto Health Center. The method used is a quantitative research with a cross-sectional design. The research sample amounted to 95 patients who were selected using the purposive sampling technique. Data collection was conducted using a structured questionnaire that measured the level of knowledge about hypertension and chronic kidney failure prevention behaviors. The data were analyzed univariate and bivariate using the spearman rank test with a significance level of 5%. The results showed that most of the respondents were at a good level of knowledge and the majority had good kidney failure prevention behaviors. Bivariate analysis showed that there was a weak level of relationship strength (0.333) between knowledge and GGK prevention behavior in hypertensive patients at the Limboto Health Center (p < 0.05) with the direction of positive relationship. In conclusion, the higher the knowledge, the better the behavior to prevent chronic kidney failure, even though the strength of the relationship is relatively weak. This suggests that knowledge plays a role in the formation of preventive behaviors, but is not the only factor that influences them.